Merit pay : linking pay to performance in a changing world - Heneman, Robert L.; Werner, Jon M. (Emerald Publishing Limited : Information Age Pub., 2005)
This book was written to bring together a summary of the current knowledge on merit pay and to further advance understanding of this type of incentive pay plan. When the writing of the first edition was begun in 1989, there were no books devoted exclusively to the subject of merit pay. Thus, this book was written to fill a void in the compensation literature. Since then, surveys have shown that merit pay remains a frequently used method of incentive compensation, and research into the merit pay process continues to grow. However, other forms of incentive pay, such as gainsharing, continue to receive the most attention, as evidenced by the number of books and articles on this topic in the popular press. In response to the frequent use of merit pay in organizations and the growing body of research, a book-length treatment of merit pay was needed. What we hope to do with this second edition, beyond updating, is to link merit pay with the many changes going on in total compensation or "reward management" (R. Heneman, 2001a, 2002). We also will argue that, even among all the challenges and changes that organizations currently face, there is still "merit" in appropriately conceived and implemented merit pay plans (Bates, 2003c).
Keywords: Compensation management.; Merit pay.; Business & Economics -- General.; Finance and the finance industry.; Business and Management.; elektronické knihy; electronic books